2020
DOI: 10.1371/journal.pone.0241413
|View full text |Cite
|
Sign up to set email alerts
|

Phasmarhabditis zhejiangensis sp. nov. (Nematoda: Rhabditidae), a new rhabditid nematode from Zhejiang, China

Abstract: A new nematode species of the genus Phasmarhabditis was isolated from the body surface of a slug (Philomycus bilineatus Benson, PB). Morphological and molecular analyses confirmed this nematode as a new species. The nematode was named Phasmarhabditis zhejiangensis sp. nov. (Nematoda: Rhabditidae) and is dioecious. In males, the open bursa with genital papillae is characterized by the formula 1-1-1-2-1-3, and the spicule length is 58μm. In female, the vulva is located approximately in the middle of the body. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…By the shape of a female tail, the new species differs from all species of Pellioditis with a cupola-shaped tail joining a slender terminus, i.e., P. bonaquensis 1 Nermuť, Půža, Mekete & Mráček, 2016b , P. huizhouensis Huang et al 2015, P. meridionalis Ivanova & Spiridonov, 2017 , P. papillosa (Schneider, 1866) Andrássy, 1976, P. safricana Ross, Pieterse, Malan & Ivanova, 2018, and P. zhejiangensis Zhang & Liu, 2020. The female tail shape of P. thermalis n. sp.…”
Section: Resultsmentioning
confidence: 91%
“…By the shape of a female tail, the new species differs from all species of Pellioditis with a cupola-shaped tail joining a slender terminus, i.e., P. bonaquensis 1 Nermuť, Půža, Mekete & Mráček, 2016b , P. huizhouensis Huang et al 2015, P. meridionalis Ivanova & Spiridonov, 2017 , P. papillosa (Schneider, 1866) Andrássy, 1976, P. safricana Ross, Pieterse, Malan & Ivanova, 2018, and P. zhejiangensis Zhang & Liu, 2020. The female tail shape of P. thermalis n. sp.…”
Section: Resultsmentioning
confidence: 91%
“…77 Nematodes from the genus Phasmarhabditis are problematic to classify as there are some poorly described species, but currently 18 species have been isolated from terrestrial gastropods, including P. apuliae, P. bohemica, P. bonaquaense, P. californica, P. circassica, P. clausilliae, P. hermaphrodita, P. meridionalis, P. neopapillosa, P. papillosa, P. safricana, P. akhaldaba, P. kenyaensis, P. thesamica, P. quinamensis, P. zhejiangensis and P. tawfiki, and one species (P. huizhouensis) from rotting leaf litter. [78][79][80][81][82][83][84][85][86][87][88][89][90][91] There were another two Phasmarhabditis species including P. nidrosienses (isolated from a marine habitat) and P. valida (isolated from littoral detritus), 92 but after revision they were moved to the genus Buetschlinema. 93 It is clear from the numerous surveys carried out over the last 30 years that Phasmarhabditis nematodes are commonly found in many countries from diverse terrestrial gastropod hosts.…”
Section: Slug Parasitic Nematodes and The Genus Phasmarhabditismentioning
confidence: 99%
“…Moreover, international surveys have been conducted in Europe [7], Asia [43], North America [44], Australia [45] and Africa [46] to identify whether nematodes from other families are associated with molluscs as definitive hosts. Overall, it has been reported that nematode species belonging to the following eight families-Agfidae, Alaninematidae Alloionematidae, Angiostomatidae, Cosmocercidae, Diplogasteridae, Mermithidae and Rhabditidae used molluscs as definitive hosts [40,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65].…”
Section: Nematodes As a Biocontrol Agent Of Slugsmentioning
confidence: 99%